May mothers given warfarin breast-feed their infants? - Orme, M L (1977)
Warfarin was measured with a sensitive and specific method in the plasma and breast milk of 13 mothers. Less than 0-08 micronmol warfarin per litre (25 ng/ml) of breast milk was found in each instance. Seven of the mothers were breast-feeding their infants, in none of whom was warfarin detected in the plasma; furthermore, in three the British corrected ratio of the plasma was appreciably less than that of the mother and was within the expected range. We conclude that nursing mothers given warfarin may safely breast-feed their infants.